Вітчизняний та світовий досвід України у виробництві пива - Домарецький, Віталій Афанасійович; Куц, Анатолій Михайлович; Карпутіна, Маргарита Віталіївна; Мельник, Ірина (My University, 2012)
Проаналізовано динаміку виробництва пива у світі та в Україні протягом 2005-2010 років. Оцінені фактори, які впливають на цінову політику у галузі, на обсяги виробництва вітчизняного пива, на величину імпорту та експорту цього напою. Окреслені задачі, які стоять перед пивоварною галуззю на сучасному етапі. The dynamics of production of beer is analysed in the world and in Ukraine during 2005 - 2010. The row of factors influences on a price policy in industry, on a production of beer volume, on an import and export of this drink. These factors were appraised. Tasks which stand before brewing industry on the modern stage are outlined. To such tasks behave: improvement of high - quality indexes of the prepared product, introduction of energy saving technologies in the production of beer, development of new types of the cheap and ecologically clean packing.
Keywords: імпорт; експорт пива; динаміка ринку пива; import; export of beer; dynamics of market of beer; кафедра біотехнології продуктів бродіння і виноробства